2021
DOI: 10.1155/2021/2789481
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of YTH Domain Family in Lung Adenocarcinoma: Expression Profile, Association with Prognostic Value, and Immune Infiltration

Abstract: Background. All YTH domain family members are m6A reader proteins accounting for the methylation modulation involved in the process of tumorgenesis and tumor progression. However, the expression profiles and roles of the YTH domain family in lung adenocarcinoma (LUAD) remain to be further illustrated. Methods. GEPIA2 and TNMplot databases were used to generate the expression profiles of the YTH family. Kaplan-Meier plotter database was employed to analysis the prognostic value of the YTH family. Coexpression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…We conducted gene ontology (GO) analysis and pathway enrichment analysis to characterize the biological mechanisms and signaling pathways of common host factor networks. GO biological processes and GO molecular functions are drawn by the WEB-based genome analysis toolkit webgestalt ( Hu et al, 2021 ) ( http://www.webgestalt.org/ ), and the KEGG pathway analysis results are generated by R and clusterprofiler ( Yu et al, 2012 ) package. A cutoff of Benjamini-Hochberg adjusted p -values < 0.05 was adopted in this apart.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted gene ontology (GO) analysis and pathway enrichment analysis to characterize the biological mechanisms and signaling pathways of common host factor networks. GO biological processes and GO molecular functions are drawn by the WEB-based genome analysis toolkit webgestalt ( Hu et al, 2021 ) ( http://www.webgestalt.org/ ), and the KEGG pathway analysis results are generated by R and clusterprofiler ( Yu et al, 2012 ) package. A cutoff of Benjamini-Hochberg adjusted p -values < 0.05 was adopted in this apart.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the recognition that there are both m6A-dependent and m6A-independent mechanisms involved in DDR and further understanding of these pathways may be helpful for the development of potential novel therapies. Aberrant m6A modification is prevalent in various types of cancer and is associated with patient prognosis (Hu et al, 2021; W. Li et al, 2022; Meng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that in some cancer types, the infiltration of lymphocytes, especially CD4 + T cells and CD8 + T cells, was associated with the activation of immune responses and resulted in favorable prognosis. Meanwhile, the tumor lesion infiltration of large numbers of tumor-associated neutrophils may induce inflammation and stimulate tumor progression and metastasis, thus inhibiting anti-tumor T-cell responses [ 55 , 56 ]. Macrophages are multifunctional immune cells that have the function of phagocytosis and digestion of foreign substances.…”
Section: Discussionmentioning
confidence: 99%